Comparison of Principles in Rental Agreements According to the Civil Code and KHES - Anggi Wirakusuma; Amanda Syafani Al Ikhsan Hasibuan; Adhitya Aldhani Wijaya; Muhammad Yasir Azhar; Muhammad Asdon Munthe (Jurnal Cendikia ISNU SU, 2025)
This study discusses the comparison of legal principles in rental agreements according to the Civil Code (KUHPerdata) and the Compilation of Sharia Economic Law (KHES). The background of this study is the importance of understanding the differences and similarities between the two legal systems applicable in Indonesia, especially in the context of a pluralistic society. The research method used is normative research with a comparative approach, through analysis of legal documents, literature, and related case studies. The research stages include identifying the main principles in the Civil Code and KHES, comparing the principles of freedom of contract, consensualism, good faith, and justice and welfare. The results of the study indicate that the principle of freedom of contract in the Civil Code is more flexible than the KHES which is limited by sharia values. The principles of consensualism and good faith are applied differently, with the KHES adding unique moral and religious dimensions. The conclusion of this study confirms that the KHES places more emphasis on justice and welfare in every agreement, while the Civil Code focuses on legal certainty. These findings are relevant to understanding the application of law in pluralistic societies and enhancing harmony between the two legal systems.